The Politics and Economics of Globalization and Social Change in Radical Adult Education: A Critical Review of Recent Literature - John D. Holst (Adult Education Research Conference, 2006)
This review analyzes perspectives on globalization within radical adult education focusing on how perspectives of the globalization process affect people’s understanding of the nature and agents of social change. It argues that new movements move us beyond the limits in current globalization perspectives.
Keywords: Radical Adult education; Globalization; Social Movements; Civil Society